ANALISIS OPTIMASI PENGELOLAAN AIR IRIGASI PADA BENDUNG DI SUNGAI BEDOG - , Aniessa Rinny Asnaning ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bedog River is one of the major rivers through the province of Yogyakarta Special Region. There are several series of weir operated for the irrigation purpose which among others are Cokrobedog, Gamping, and Pendowo weir. In the water management for irrigation within weirs, there are many problems encountered in order to fullfil the water demand. An insufficient of water supply for irrigation can be caused due to lack of both coordination and regulation. This problem especially occured in Gamping irrigation area where in the downstream area extremely lack of water supply that causing agricultural productivity decreases. Optimization analysis on Gamping irrigation area is performed by using linear programming method by shifting cropping schedule that fits to the cropping pattern condition in the field.The net benefit is obtained from the optimum planting area based on production cost and selling price in accordance with the unit price at the farmer level. Optimization analysis result indicates that the cropping pattern of paddy- paddy-paddy with first crop that started in the second half of February generates the maximum net benefit of about Rp 19.937.000.000,- and cropping intensity of 281%. The minimum net benefit of about Rp 17.895.000.000,- is achieved when cropping pattern of paddy-paddy-paddy on first crop is started in first half of January with a cropping intensity of 251%. The trend test using Mann-Kendall Method shows that the shifting of first crop has no significant effect on the increase and decrease of the maximum net benefit because of fixed trend. The sensitivity analysis shows the maximum net benefit of about Rp 21.680.000,- occurred when the selling price is maximum and the cost is minimum, and the minimum net benefit of about Rp 18.845.000,- occurred when the selling price is minimum and the cost is maximum. Water management in the Bedog River within three weirs would be more optimal when the first crop starts in the second half of February.